Building and codifying a scale of the level of tactical performance of advanced volleyball players - Mohammed, Khaleel Sattar; Flayyih, Mohammed Salih; Rumeeh, Ammar Fleah (International Journal of Psychosocial Rehabilitation, 2020)
The research objectives, to build a measure of the level of tactical performance of volleyball players applying for the Iraqi Premier League for the 2018-2019 season. The nature of the research problem, then the researchers determined the research sample in the deliberate manner of the players of the Iraqi clubs for the Premier League (B, A). The researchers adopted the entire community as a sample for the research, and the number (156) players distributed over (13) clubs and divided the sample into (12)players an exploratory experiment player representing (the police club) and (100) player representing the construction sample and after a maximum period of two months has passed since applying the scale to the construction sample the researchers applied it to the rationing sample as it consisted of (144) players which is the same as the construction sample plus the rest of it The remaining number, which is (44) players, the researchers extracted the grades and the standard levels. The researchers reached several conclusions, the most important of which was: Building a measure of the level of linear performance by (36) items. The scale was also legalized in the final form, and the standard grades and levels were extracted for it. The researchers recommended using the current scale of volleyball coaches to identify the level of the sample in order to develop their own plans to improve or improve the level of planning performance. Building a measure of the level of the plan’s performance level of volleyball players for other samples and from different age groups.